Population Development and Evolving Technology in Nepal: A Comparative Analysis (Journal of Population and Development, 2024)
Technological advancements have significantly influenced population development in Nepal, impacting healthcare, economic growth, education, urbanization, and environmental sustainability. This paper explores these influences through a comparative analysis of historical and contemporary data. The study investigates the role of technology in improving life expectancy, reducing infant mortality, creating job opportunities, and enhancing educational access. Additionally, it examines the development of smart cities and the adoption of sustainable practices. The research utilizes a mixed-methods approach, incorporating quantitative data from national and international sources, and qualitative insights from expert interviews. The findings reveal that while technological adoption is accelerating, disparities persist, particularly between urban and rural areas. Recommendations include expanding digital infrastructure, enhancing STEM education, and fostering innovation to ensure inclusive and sustainable growth. This study contributes to understanding how technology can be leveraged to optimize population development in Nepal.